EGAKAN BAMBU DIKEBUN RAKYAT KOTAMADYA SALATIGA - Elizabeth A Widjaja; Sunaryo Sunaryo; Hamzah Hamzah (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Bamboo is one of the important and favorite plants in the villages, however the management of this plant is less interest either from the people or even the government. Because of that there are many bamboo garden has been turned into housing or industrial area, although some people understand that bamboo can be used to prevent soil erosion as well as water conservation. In Central Java, bamboo is mainly used to make furniture, whereas the bamboo handicrafts is only made by the local people for daily uses.The uses of bamboo for handicraft is mainly occurred in Yogyakarta Province, although the bamboo material for this purposes is imported from Central Java. Because of that a study on the bamboo stand in Central Java Province is very important to support the furniture industry which is found also in this neighbouring city. Based on a study done at the Promasan Village, Salatiga, it is found that the bamboo stand occurred in the plot (50 m x 50 m, 5 plots) was 332.96 clum/ha on 2003, whereas the bamboo stands on 2004 decreased till 331.2 clump/ha. The number of clump might decrease due to over harvesting, so many clump was died. The same phenomena was also occurred at the bamboo potency on 2004 which was decreasing compare to 2003 data. The bamboo potency/clump might be increased, but the total production of bamboo culm/ha/year was decreasing sharply compare to the bamboo condition on 2003. This situation can be seen also from the regeneration of bamboo which was decreasing compare the data on 2003 to 2004. The species found in this village was bambu tali (Gigantochloa apus), which was dominated at this village. This potency of this bamboo stands is very high, because the local people used this bamboo for daily use and it used more than other species.However,Gigantochloa atter has also a demand for the bamboo furniture, because of that the potency of this species is also high.Then Dendrocalamus asper which also been used for bamboo furniture. The potency of Bambusa vulgaris is very low in this village, because this species was rarely used.